Topological Optimization and Optimal Transport: In the Applied Sciences - Bergounioux, Maïtine; Oudet, Édouard; Rumpf, Martin; Carlier, Guillaume; Champion, Thierry; Santambrogio, Filippo (Radon Series on Computational and Applied Mathematics, 2017)
By discussing topics such as shape representations, relaxation theory and optimal transport, trends and synergies of mathematical tools required for optimization of geometry and topology of shapes are explored.